2020
DOI: 10.17523/bia.2020.v77.e1469
|View full text |Cite
|
Sign up to set email alerts
|

Escore visual como uma ferramenta eficiente para identificação de bovinos precoces

Abstract: A b s t r a c tThe hypothesis tested was that it is possible to identify animals that deposit fat and muscle earlier through indirect evaluation. Thus, the objective of this work was to evaluate the use of visual evaluation of precocity score for the identification of Nelore heifers with an early biotype. Eighteen Nelore heifers aged 9 to 11 months were evaluated visually for body structure (S), precocity (P), and muscle (M) scores. The animals were divided according to precocity scores: animals with scores 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…The mean ± standard deviation estimated for body measurements were: HG (201.35 ± 14.99), BL (102.26 ± 11.89) and BV (333.62 ± 58.51). In general, the mean values of body measurements found in this study are consistent with those reported in female Murrah crossbred buffalo raised in Brazil (Melo et al, 2018, 2020 and India (Dhillod et al, 2017). Melo et al (2018) phenotypically describe the females of this buffalo breed as animals with long and wide chests, medium to long rumps, medium height, deep animals and long diagonal lines, which contribute positively to their reproductive and productive abilities.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The mean ± standard deviation estimated for body measurements were: HG (201.35 ± 14.99), BL (102.26 ± 11.89) and BV (333.62 ± 58.51). In general, the mean values of body measurements found in this study are consistent with those reported in female Murrah crossbred buffalo raised in Brazil (Melo et al, 2018, 2020 and India (Dhillod et al, 2017). Melo et al (2018) phenotypically describe the females of this buffalo breed as animals with long and wide chests, medium to long rumps, medium height, deep animals and long diagonal lines, which contribute positively to their reproductive and productive abilities.…”
Section: Resultssupporting
confidence: 90%
“…In particular, the growth rate is an important parameter in animal production, as it characterizes the adaptability and economic suitability of livestock production (Ağyar et al ., 2022). Animals that grow faster in terms of body weight must also initiate early physiological functioning of reproduction and milk production (Thiruvenkadan et al ., 2009; Gurgel et al ., 2020). However, the uncontrolled increase in weight and body size of the animal leads to reproductive problems and increases production costs, due to the greater energy demand for its maintenance (Melo et al ., 2020).…”
mentioning
confidence: 99%
“…The measures evaluated in this research were influenced by environmental factors such as race, sexual status, age, and nutritional management (Oliveira et al 2017;Gurgel et al 2020;Vaz et al 2022), which justifies the variability observed in the data from this study. It should be noted that a diversified database is desirable to improve the predictive capacity and comprehensiveness of the generated equations (Menezes et al 2015;Gomes et al 2021;Gurgel et al 2021).…”
Section: Discussionsupporting
confidence: 61%
“…-Reducing the reproduction cycle Growth, reproduction and finishing precocities are important for reducing the cattle raising cycle, for greater capital turnover and, consequently, for greater efficiency in the activity. Precocity can be understood as the speed at which cattle reach puberty (Gurgel et al, 2020), when bone growth is completed and most of the muscles are formed. At puberty, the growth hormones responsible for growing bone and muscle tissue are replaced by sex hormones, when females enter estrus and males have an increase in their scrotal circumference.…”
Section: Opportunitiesmentioning
confidence: 99%